1983
DOI: 10.1136/ard.42.3.311
|View full text |Cite
|
Sign up to set email alerts
|

Polymyalgia rheumatica: an arthroscopic study of the shoulder joint.

Abstract: SUMMARY A careful selection of 19 patients fitting the classical description of polymyalgia rheumatica have been examined by arthroscopy and thoroughly screened and followed up to exclude rheumatoid arthritis and other disease processes. Synovitis of the shoulder joint has been observed through the arthroscope in 17 and synovitis of varying degrees noted histologically, 4 of whom were studied by immunofluorescence. Five patients had radioactive joint scans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

1984
1984
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…The presence of proximal articular and periarticular synovitis in PMR has been proven by arthroscopy, 8 synovial biopsy, 9,10 ultrasonography (US), 11,12 scintigraphy, 13 and magnetic resonance imaging (MRI). 14 Using US and MRI of the shoulders, Cantini et al showed that subacromial and subdeltoid (SA-SD) bursal synovitis (= bursitis) is the most frequent and unique lesion present in almost all PMR patients.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of proximal articular and periarticular synovitis in PMR has been proven by arthroscopy, 8 synovial biopsy, 9,10 ultrasonography (US), 11,12 scintigraphy, 13 and magnetic resonance imaging (MRI). 14 Using US and MRI of the shoulders, Cantini et al showed that subacromial and subdeltoid (SA-SD) bursal synovitis (= bursitis) is the most frequent and unique lesion present in almost all PMR patients.…”
Section: Introductionmentioning
confidence: 99%
“…Polymyalgia rheumatica (PMR) is a common inflammatory disease in the elderly, which is characterized clinically by pain and stiffness ascribed to multiple tenosynovitis in the proximal muscles (1)(2)(3). Corticosteroid therapy usually shows good therapeutic effects at a low to moderate dosage within a week after initiation in PMR, but in some cases muscle symptoms persist even though C-reactive protein (CRP) and erythrocyte sedimentation rate (ESR) return to the normal range (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…However, many patients appear to have PMR alone. In recent studies, in¯ammation of the shoulder regions has been demonstrated by arthroscopy and ultrasonography [13,14,20]. The etiology of the synovitis remains elusive; the pathogenesis is thought to be immune-mediated [11].…”
Section: Discussionmentioning
confidence: 98%